An Investigation of Building Seismic Design Parameters in Mataram City Using Lombok Earthquake 2018 Ground Motion - Ni Nyoman Kencanawati; Didi Supriyadi Agustawijaya; Rian Mahendra Taruna (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Mataram is the capital of West Nusa Tenggara. West Nusa Tenggara is made up of two islands, Lombok and Sumbawa. The 2018 earthquake on Lombok undoubtedly affected spectral acceleration. This is an important factor to be addressed in structural design. Short-period spectral acceleration, SS,increases 18.323% compared to the value listed in seismic code SNI 1976:2012, corresponding to a 2500-year return period. However, even if the SS value increases, the design category of the building does not change and remains in the D category. In general, the acceleration value in this study was found to be relatively greater than that of the existing code for periods of less than 0.462 s for site class D and in periods of less than 0.830 s in site class E. In addition, the seismic response coefficient, CS, for medium soil increases by 10.782% compared to the CS calculated using of the current code. This effect is more severe in soft soil areas, where the increase reaches 13.168%. Improving existing codes with seismic design parameters for new buildings affected by the ground motion of recent strong earthquakes will lead to more preparedness and will be an important part of local disaster risk reduction.